Legal Protection Of Indigenous Peoples In East Kalimantan In The Development Of The Archipelago's Capital City Associated With Applicable Laws And Regulations In Indonesia - Rusdianto, Karin; Septina Basani, Christin (Fakultas Hukum Dehasen, 2025)
This study examines the protection of indigenous peoples in the Nusantara Capital City (IKN) in the context of sustainable development in Indonesia, focusing on the roles, rights, and challenges faced. Using normative research methods with a statutory approach and a conceptual approach, this study analyzes the legal framework that governs indigenous peoples, such as Article 18B paragraph (2) of the 1945 Constitution, Law No. 39 of 1999 concerning Human Rights and the Law on Villages. This research uses the theory of legal protection and implementation theory. The findings suggest that indigenous peoples face significant challenges, including loss of access to traditional lands, marginalization in decision-making processes, and threats to cultural identity. This study emphasizes the importance of a participatory approach that integrates local wisdom to protect the rights of indigenous peoples while supporting fair and sustainable development. This study recommends.